Understanding the origins of nucleophilic hydride reactivity of a sodium hydride-iodide composite - Hong, Zonghan (2018)
Sodium hydride (NaH) has been commonly used as a Brønsted base in chemical syntheses, while it has rarely been employed to add hydride (H¢) to unsaturated electrophiles. We previously developed a procedure to activate NaH through the addition of a soluble iodide source and found that the new NaH–NaI composite can effect even stereoselective nucleophilic hydride reductions of nitriles, imines, and carbonyl compounds. In this work, we report that mixing NaH with NaI or LiI in tetrahydrofuran (THF) as a solvent provides a new inorganic composite, which consists of NaI interspersed with activated NaH, as revealed by powder X-ray diffraction, and both solid-state NMR and X-ray photoelectron spectroscopies. DFT calculations imply that this remarkably simple inorganic composite, which is comprised of NaH and NaI, gains nucleophilic hydridic character similar to covalent hydrides, resulting in unprecedented and unique hydride donor chemical reactivity.